2006
DOI: 10.1002/adem.200600078
|View full text |Cite
|
Sign up to set email alerts
|

Iron Based Cellular Structures – Status and Prospects

Abstract: Cellular metals based on iron have been intensively investigated during the last two decades. Because of the significant decrease in of the structural density of iron based cellular structures, numerous technologies have been developed for their manufacturing. Besides the tremendous weight reduction a combination with other properties like energy and noise absorption, heat insulation and mechanical damping can be achieved. This contribution will give an overview about the latest state in iron based cellular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 1 publication
0
25
0
1
Order By: Relevance
“…Investigating the influence of density, cell size and cell shape on the mechanical properties of open cell 6101 aluminum foams, Nieh et al [31] found that, under similar densities, cell size does not have any significant effect on strength while the cell shape had some influences [31]. On the other hand, there have been researchers who found the cell sizes would affect the mechanical properties of the foam or that of a lattice structure [32,33].…”
Section: Effect Of Structural Properties On Elastic and Plastic Comprmentioning
confidence: 99%
“…Investigating the influence of density, cell size and cell shape on the mechanical properties of open cell 6101 aluminum foams, Nieh et al [31] found that, under similar densities, cell size does not have any significant effect on strength while the cell shape had some influences [31]. On the other hand, there have been researchers who found the cell sizes would affect the mechanical properties of the foam or that of a lattice structure [32,33].…”
Section: Effect Of Structural Properties On Elastic and Plastic Comprmentioning
confidence: 99%
“…The walls can be sintered to be fully dense as well as porous [95,96]. MHSs are known to have a good energy absorbing capability [97].…”
Section: Hybrid Wire-woven Metalsmentioning
confidence: 99%
“…In principle, cellular metals can be manufactured from gas, liquid, or solid phases and currently the most advanced methods involve meltmetallurgical processes. [5] Several groups have produced foam structures by using hollow spheres to form the cells of the material. [6,7] These materials exhibited plateau stresses of 5 and 23 MPa, respectively, with volume specific energy absorptions SEA of 2 and 10 MJ m À3 respectively, up to 50% strain.…”
mentioning
confidence: 99%